Step closer - Cawthon, Scott, 1971-; Waggener, Andrea Rains, 1960-; Cooper, Elley; Parra, Kelly (Cawthon, Scott, 1971- Five nights at Freddy's. Fazbear frights, 2020)
"Isolation can open up a void. Pete lashes out at his younger brother in the wake of his parents' divorce, falling prey to a gruesome curse. Kasey struggles with the lengths she'll go to survive on the streets after stealing a pair of unusual novelty glasses. Samantha and her sister, Susie, struggle to exist side by side, desperate to connect after a horrific tragedy. But in the grim world of Five Nights at Freddy's, empty feelings often attract hungry monsters..."--Back cover.